Konsep Essensialisme Dalam Perspektif Filsafat Pendidikan Islam - Amin Putri, Rokhmatul Khoiro; M Yunus Abu Bakar (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Philosophy of Essentialism is a philosophical school that wants humans to return to their old culture. The emergence of this understanding was a reaction to the absolute and dogmatic symbolism of the Middle Ages. Thus, a systematic and comprehensive concept of man and the universe was drawn up, which met the requirements of the times. This essentialism views that education that is based on the view of flexibility in all its forms can be a source of the emergence of views that are changing, easily swayed, less focused and less stable. Therefore, education must be based on values ​​that can be stable and have been tested by time, durable and have values, so that education in a country can remain stable and directed. The purpose of the philosophy of essentialism education is to improve the character of the community through the existing cultural heritage, so that later students can contribute to improving people's lives in the face of changing times that can kill character values. This paper aims to examine the philosophy of essentialism in the perspective of Islamic education, using the library research method. The results of the study stated that the flow of essentialism has a view in the field of education, namely: educational goals, educational curriculum, educators, and students. Along with the times, there are several views that need to be taken seriously, namely: the ontological view, the epistemological view, and the axiological view.